2021
DOI: 10.1111/jnu.12622
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Nurse‐Led Tele‐Homecare Program for Patients With Multiple Chronic Illnesses and a High Risk for Readmission: A Randomized Controlled Trial

Abstract: Purpose Multiple chronic illnesses, such as those associated with advanced age, are leading causes of poor health, disability, death, and high healthcare expenditures. Tele‐homecare is a novel method for providing home care to patients with chronic illnesses. The purpose of this study was to evaluate the effectiveness of an integrated nurse‐led tele‐homecare program for patients with multiple chronic illnesses and a high risk for readmission. Design A randomized controlled trial. Methods Two hundred patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…A total of 9% (n=3) of studies used a mixed methods methodology [ 3 , 87 , 96 ], whereas the remaining studies (28/34, 82%) used a quantitative methodological approach. Of the 28 quantitative studies, 8 (n=8, 28%) used a randomized controlled trial design [ 89 , 90 , 97 , 101 , 106 , 107 , 109 , 110 ]. Other quantitative studies have used observational or nonrandomized trial designs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 9% (n=3) of studies used a mixed methods methodology [ 3 , 87 , 96 ], whereas the remaining studies (28/34, 82%) used a quantitative methodological approach. Of the 28 quantitative studies, 8 (n=8, 28%) used a randomized controlled trial design [ 89 , 90 , 97 , 101 , 106 , 107 , 109 , 110 ]. Other quantitative studies have used observational or nonrandomized trial designs.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic health records and databases [ 79 , 81 , 95 , 97 , 98 , 102 , 104 ] have been widely used for digital innovation. The use of wearable body sensors or devices [ 80 , 99 , 107 ], web-based chatting platforms [ 82 ], and automated emails [ 109 ] were less common.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A French, Level 2 RCT described in the Telemedicine section confirmed that remote monitoring for wound care via home healthcare had the same good outcomes as in‐person clinic care 79 . In a Level 2 RCT that was carried out in Taiwan before the pandemic, Liang et al demonstrated that nurse‐led remote home care provided to 100 patients with chronic illnesses was more effective than traditional homecare provided to 100 patients, with significantly reduced mortality (8% vs. 19%, p = 0.027) and emergency department visits (12% vs. 26%, p = 0.013) at 6 weeks 91 . Remote home care involved 24/7 remote monitoring and surveillance using a one‐touch smartphone, blood pressure monitor, glucometer (for diabetes), medication dispenser, and a necklace emergency call button.…”
Section: Resultsmentioning
confidence: 99%